Long‐term patient reported outcomes of elbow, wrist and hand surgery for rheumatoid arthritis. (5th September 2018) - Okura, Chisa; Ishikawa, Hajime; Abe, Asami; Yonemoto, Yukio; Okamura, Koichi; Suto, Takahito; Oyakawa, Tomo; Miyagawa, Yusuke; Otani, Hiroshi; Ito, Satoshi; Kobayashi, Daisuke; Nakazono, Kiyoshi; et al.
Abstract: Aim: A retrospective questionnaire survey was conducted to investigate the long‐term outcomes of elbow, wrist and hand surgery for rheumatoid arthritis (RA). Methods: One hundred and thirteen RA patients underwent primary elective elbow, wrist or hand surgery at our hospital between January 2002 and December 2003. To evaluate the outcomes at 10 years after surgery, the patient‐reported outcomes were assessed using an original questionnaire that inquired about the site of treatment; the modified Stanford Health Assessment Questionnaire (mHAQ) was also used. Results: Responses were obtained from 67 patients (98 sites). In the 10 years after surgery, the Disease Activity Score of 28 joint – erythrocyte sedimentation rate (4) and the modified Health Assessment Questionnaire scores of the patients showed significant improvement. Nearly 85% of patients were satisfied with the outcome at the surgical site. The most frequent reason for perceived improvement was 'pain relief' (all surgical sites). An 'improved appearance' was frequently reported after finger surgery and 'increased power' was frequently reported after wrist and thumb surgeries. With regard to elbow surgery, 30% of the patients were satisfied with the increase in motion and power. In contrast, approximately 20% of patients complained of decreased power around the surgical site after elbow and thumb surgeries. Conclusions: Our original patient‐reported outcome assessment tool revealed that elbow, wrist and hand surgery provided long‐lasting benefits in RA patients. While the efficacy differed in some of the surgical sites, pain relief was the most favorable effect. Altered medical therapy may also have impacted the patient‐perceived outcomes of surgery at 10 years.